2015
DOI: 10.4000/apliut.5184
|View full text |Cite
|
Sign up to set email alerts
|

Assessing undergraduate student engagement in a virtual resource center

Abstract: International audienceThis contribution seeks to better understand undergraduate students’ perceptions of and engagement in a virtual resource center for Business English and the links between the use of the center and English language learning. In order to assess student engagement in the virtual resource center, we have conducted a representative questionnaire study. The results show that there is a complex relationship between perceptions and actions and that even when students claim to perceive tools as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies on students' and teachers' representations (McAllister & Narcy-Combes, 2015;McAllister et al, 2012;Narcy-Combes & McAllister, 2011; on the development of accuracy, fluency, and complexity of written production between the beginning and the end of the programme (McAllister, 2013;McAllister & Belan, 2014) and on the students' use of the virtual resource center (McAllister, 2013;Starkey-Perret, McAllister, Belan, & Ngo, 2015) showed that although the programme is generally appreciated for the opportunities it generates for small-group interaction (McAllister et al, 2012;Starkey-Perret et al, 2012), students and teachers tend to prefer a PPP approach, claiming that TBLT does not leave sufficient room for FonF (Belan & Buck, 2012;McAllister, 2013). Questionnaire studies carried out with the students showed that the way 'grammar' is dealt with is the least satisfactory element of the programme and that there simply is not enough FonF (Belan & Buck, 2012).…”
Section: Student and Teacher Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on students' and teachers' representations (McAllister & Narcy-Combes, 2015;McAllister et al, 2012;Narcy-Combes & McAllister, 2011; on the development of accuracy, fluency, and complexity of written production between the beginning and the end of the programme (McAllister, 2013;McAllister & Belan, 2014) and on the students' use of the virtual resource center (McAllister, 2013;Starkey-Perret, McAllister, Belan, & Ngo, 2015) showed that although the programme is generally appreciated for the opportunities it generates for small-group interaction (McAllister et al, 2012;Starkey-Perret et al, 2012), students and teachers tend to prefer a PPP approach, claiming that TBLT does not leave sufficient room for FonF (Belan & Buck, 2012;McAllister, 2013). Questionnaire studies carried out with the students showed that the way 'grammar' is dealt with is the least satisfactory element of the programme and that there simply is not enough FonF (Belan & Buck, 2012).…”
Section: Student and Teacher Representationsmentioning
confidence: 99%
“…Studies also showed that the VRC is underexploited by the students, which implies that they do not do the individual post-task form-focussed activities, which makes it difficult to assess the VRC's effects on language development (McAllister, 2013;Starkey-Perret et al, 2015). A questionnaire study showed that just under half of the students (48%) visited the VRC, 66% of whom used it between one and three times over the course of the semester for a duration of under 30 minutes each time (Starkey-Perret et al, 2015). However, it was noted in the same study that the students who used the VRC found it useful for learning and that the more they used it, the more they found it useful.…”
Section: Student and Teacher Representationsmentioning
confidence: 99%